Analisis Daya Saing Kelapa Sawit di Indonesia: Studi Kasus di Kabupaten Mamuju Tengah, Provinsi Sulawesi Barat: Analysis of Indonesian Palm Oil Competitiveness: A Case Study from Central Mamuju, West Sulawesi - Pebrianto, Agung Rimba; Angka, Andi Werawe; Karim, Ikawati; Abdullah, Muhammad Arafat (Journal of Integrated Agribusiness, 2024)
The quality of crude palm oil, price, and quality of fresh fruit bunches are important factors in determining the competitive advantage of palm oil. In Central Mamuju, palm oil is processed into two main products: Crude Palm Oil (CPO) and Palm Kernel Oil (PKO), which are further refined into various derivative products like cosmetics, soap, cooking oil, and much of the CPO is directly exported, affirming its potential in the global market. This study aims to assess the impact and components of palm oil competitiveness using the diamond porter model. Results indicate that factors like resource condition availability (X1), related and supporting industries (X3), company strategy, structure, competition (X4), and government role (X5) positively influence competitiveness. However, demand conditions (X2) and opportunities (X6) negatively correlate. The competitive strengths of palm oil in this region include high-quality fresh fruit bunches and CPO, as well as competitive fresh fruit bunch prices. The presence of palm oil companies here also demonstrates high competition levels.